DAYA HAMBAT EKSTRAK BIJI JINTAN PUTIH (CUMINUM CYMINUM) DAN BIJI PALA (MYRISTICA FRAGRANS) TERHADAP JAMUR PUTIH FUSARIUM OXYSPORUM F.SP. VANILLAE PADA MEDIA PDA DAN PEMBIBITAN TANAMAN PANILI - SUDARMA, I MADE (AGRITROP; Vol. 24, No. 4 Desember 2005, 2012)
Stem rot disease on vanilla caused by Fusarium oxysporum f.sp. vanillae has been known as the most destructive disease on vanilla in Bali since 1992. A drastic disease of vanilla cultivation areas and vanilla production occurred during 1991 to 2001 resulted from the disease. The vanilla cultivation areas has been decreased about 91% and the production of vanilla bean has also been decrease about 98% during that period. Many effort have been done to control the disease such as the use of synthetic fungicide, cultural practice, etc., but until now the disease is still can not be controlled appropriately. In order to find other alternatives for controlling the disease, seeds of plants were studied for their bioactivity against Fusarium oxysporum f.sp. vanillae. Of these, the seed extracts of C. cyminum and M. fragrans showed their inhibitory activity 77.35% and 62.13% against this fungus on potato dextrose agar (PDA) medium at concentration of 0.5% (w/v). On a green house experiment, application of the seed extract into the soil at the concentration of 0.5% (w/v) (in the process of seedling preparation) obviously inhibited the development of the population of this fungus, their inhibitory activity 99.9%. These result suggested that the seed extracts of Jintan Putih ( C. cyminum) dan Pala (M. fragrans) potentially can be used to control stem rot disease on vanilla.
Keywords: inhibitory activity, stem rot disease, vanilla